1996
DOI: 10.1103/physrevlett.76.499
|View full text |Cite
|
Sign up to set email alerts
|

Charge Density Wave in Two-Dimensional Electron Liquid in Weak Magnetic Field

Abstract: We study the ground state of a clean two-dimensional electron liquid in a weak magnetic field where N ≫ 1 lower Landau levels are completely filled and the upper level is partially filled. It is shown that the electrons at the upper Landau level form domains with filling factor equal to one and zero. The domains alternate with a spatial period of order of the cyclotron radius, which is much larger than the interparticle distance at the upper Landau level. The one-particle density of states, which can be probed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
611
2
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(656 citation statements)
references
References 31 publications
36
611
2
3
Order By: Relevance
“…Upon closer examination, we find that the momenta of the quasidegenerate states are of the form (k x , 0), indicating linear order along x-direction. This is known to be one of the signatures of the stripe phase [42][43][44][45][46] .…”
Section: Resultsmentioning
confidence: 99%
“…Upon closer examination, we find that the momenta of the quasidegenerate states are of the form (k x , 0), indicating linear order along x-direction. This is known to be one of the signatures of the stripe phase [42][43][44][45][46] .…”
Section: Resultsmentioning
confidence: 99%
“…[34,35,36,37,38,39,40]). Recent work on these interesting phases of the two-dimensional electron gas has revealed that magnetic symmetry plays a crucial role in low-energy dynamics of these states.…”
Section: Discussionmentioning
confidence: 99%
“…That raises the question whether the reentrant states in the second Landau level are of equal nature as the bubble phases in higher levels. Initially, theories did not consider the second Landau level for bubble phase formation at all [93,94]. This deficiency was remedied more recently [5,119].…”
Section: Reentrant States In the 2nd Landau Levelmentioning
confidence: 99%
“…The gain in exchange energy, however, is rather determined by the modulation of the filling factor [93]. In total, the 2DES can minimize its energy by modulating the electron density at certain filling factors of the topmost occupied Landau level branch [92][93][94]. The average filling factor determines the phase symmetry, i.e.…”
Section: Density Modulated Phases In the Quantum Hall Regimementioning
confidence: 99%
See 1 more Smart Citation